Pseudoaneurysm of cystic artery after laparoscopic cholecystectomy - De Molla Neto, O. L. (2006)
Background. The formation of a pseudoaneurysm of the cystic artery is a rare occurrence after laparoscopic cholecystectomy. Case outline. Seven weeks after laparoscopic cholecystectomy, a 31-year-old woman presented with a picture of obstructive jaundice. The diagnosis of cystic artery aneurysm was verified by arteriography, CT and MRCP. At laparotomy the pseudoaneurysm was found to be compressing the common bile duct. It was successfully managed by ligation of the right hepatic artery. Discussion. Although this complication is rare, the surgeon must have a high index of suspicion to make the diagnosis.